Conversão térmica de casca de arroz à baixa temperatura: produção de bioóleo e resíduo sílico-carbonoso adsorvente - Diniz, Juraci (2005)
The exploitation of rice husks through thermal conversion at low temperature, adding economical value through its pyrolysis products, may represent a solution to the current environmental problem of discharging this agricultural residue. Dry, ground and granulometrically classified rice husks were submitted to pyrolysis at bench scale, in a fixed bed reactor, at a maximum temperature of 440 oC. The thermal conversion was made in an inert atmosphere (N2) that also served as a dragging gas, determining the time of permanence of the gases inside the system. The products, after cooling in the reactor exit, were collected and separated in fractions, to evaluate yields related to the previous established parameters. Gaseous products (gases of mean heat value), liquids (aqueous and bio-oil) and solids (silicon-carbonous residues) were obtained. The solid and liquid products were submitted to many characterization tests. The bio-oil samples were analyzed by techniques of Nuclear Magnetic Resonance (NMR) of 1H and 13C; Gas Chromatography coupled to Mass Spectrometry (GC-MS); Infrared (IR) and Ultraviolet (UV) Spectrophotometry; Fluorescence Spectrophotometry (FS) and Electronic Paramagnetic Resonance (EPR). Elemental analysis was done and the High Heating Value (HHV) was determined. Bio-oil and aqueous fraction were also submitted to tests of biodegradability and toxicity with the aid of test animals (mice and lizards). The silica-carbonous residue was submitted to adsorption tests (acetic acid, textile dyes and carbohydrates) and characterization (iodine-methylen blue- and phenazone-number); BET analysis; Blaine test; IR Spectrophotometry; X-Ray Diffraction (XRD); Scanning Electronic Microscopy (SEM); High Resolution Spectroscopy of Solid-State Nuclear Magnetic Resonance of 13C and 29Si (HR/SSNMR) and High Heating Value (HHV). The silica, resultant from calcination of silica-carbonous residue was also submitted to adsorption tests (textile dyes and carbohydrates) and characterization (methylen blue-number); X-ray Diffraction (XRD); Scanning Electronic Microscopy (SEM); High Resolution Spectroscopy of Solid-State Nuclear Magnetic Resonance in the of 29Si (HR/SSNMR) and Blaine test. In the pyrolysis study it was observed that, with the rising of the process temperature, the yield of the gases formed also increases. The aqueous fraction formation rises with the temperature up to 440 oC; above such a temperature, there is a reduction on the aqueous fraction. Yet the bio-oil production rises up to the temperature of 420 oC, higher temperatures than this reduce the bio-oil production. The yield on silica-carbonous residue decreases continually as the process temperature increases. The silicon-carbonous residue and the silica has adsorbent properties. It was determined that in the liquid oily fraction oxygenated compounds predominate, mainly phenols, highliting the presence of mixed function showing ethers, esters, ketones, aldehydes, alcohols, among others. The presence of such compounds in its constitution allows the use of bio-oil in the production of resins, replacement of the petrochemical phenol, as a substitute for fuel oil and as an additive for diesel oil. The high number of compounds present in the bio-oil makes the identification and determination of chemical species a task beyond the objective of this paper. The bio-oil obtained (distilled or not distilled) presented low text of humidity. Analytical tests had shown that the distillation of the liquid fraction modifies the composition of the bio-oil. The necessary heating for the distillation generates free radicals, reduces the carbon text and the hydrogen and, consequently it rises the oxygen text. The bio-oil, separated for distillation, was presented highly viscous and reactive, polymerizing easily in contact with atmospheric air.